The European Parliament as an Accountability Forum Overseeing the Economic and Monetary Union - Akbik, Adina (Social Sciences, 2022)
This book targets scholars and students of European integration interested in democratic accountability in the EU and the reforms introduced since the euro crisis. It fits the syllabi of courses on EU institutions and EU economic governance taught from different disciplinary perspectives, including political science, law, and political economy.